Activated carbon from a specific plant precursor biomass for hazardous Cr(VI) adsorption and recovery studies in batch and column reactors: Isotherm and kinetic modeling. (December 2020) - Haroon, Hajira; Shah, Jehanzeb Ali; Khan, Muhammad Saqib; Alam, Tatheer; Khan, Romana; Asad, Saeed Ahmad; Ali, Muhammad Arif; Farooq, Ghazanfar; Iqbal, Mazhar; Bilal, Muhammad
Graphical abstract: Highlights: Eucalyptus camaldulensis sawdust was proved as an excellent choice for H3 PO4 activation. The efficiency of Cr(VI) removal was reported as 87 % at pH 3.0. Mesoporous activated carbon demonstrated chemisorption and lower metal recovery. Thermodynamic, isotherms, and kinetics were studied. Bed depth service model was used to analyze the column adsorption data. Abstract: The main aim of this work was the development of the chemical activated carbon (AC) method from specific wood biomass, i.e., Eucalyptus camaldulensis sawdust (ECS), and this AC is proposed as a promising alternative treatment for hazardous Cr(VI) from aqueous solution. ECS waste sawdust was carbonized in two stages, i.e. 170 °C for 60 min, followed by 500 °C for 120 min under the continuous steam of nitrogen gas, and rated as an efficient method with H3 PO4 activation (>80% Cr(VI) removal). Finally, activated carbon- Eucalyptus camaldulensis sawdust (AC-ECS) was selected for batch and column reactor studies and different influencing parameters, such as contact time, pH, temperature, initial Cr(VI) metal concentration, particle size, and bed height were optimized. AC-ECS was characterized through analysis by SEM, EDX, FTIR, and BET. Cr(VI) adsorption was found to be highly pH-dependent, i.e., 87% at pH 3.0. AC-ECS adsorption mechanism for Cr(VI) with experimental and maximum predicted adsorption capacities of 104 and 125 mg g −1, respectively, was best described by the Langmuir isotherm (R 2 = 0.999) and pseudo-second-order kinetics (R 2 = 0.999). The column study showed an improvement in the breakthrough curve time from 5595 to 12, 270 min, with the respective increase of bed height from 5 to 15 cm, respectively. Column breakthrough data was found to be well fitted to the bed depth service time model. Current batch and column studies indicate that freshwater contamination with Cr(VI) can be managed by upscaling the AC-ECS as an efficient treatment solution.